2019
DOI: 10.1186/s12870-018-1591-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulatory network and abundant genetic variation play critical roles in heading stage of polyploidy wheat

Abstract: BackgroundThe extensive adaptability of polyploidy wheat is attributed to its complex genome, and accurately controlling heading stage is a prime target in wheat breeding process. Wheat heading stage is an essential growth and development processes since it starts at a crucial point in the transition from vegetative phase to reproductive phase.Main bodyHeading stage is mainly decided by vernalization, photoperiod, hormone (like gibberellic acid, GA), and earliness per se (Eps). As a polyploidy species, common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 93 publications
(163 reference statements)
0
39
0
Order By: Relevance
“…Additional example is the VRN1 homologs which show high allelic variation in wheat. Various mutations in VRN1, including mutations induced by TE insertions, were found to influence heading stage in wheat, as reviewed by Shi et al (2019).…”
Section: Impact Of Tes On Gene Expression and Functionmentioning
confidence: 99%
“…Additional example is the VRN1 homologs which show high allelic variation in wheat. Various mutations in VRN1, including mutations induced by TE insertions, were found to influence heading stage in wheat, as reviewed by Shi et al (2019).…”
Section: Impact Of Tes On Gene Expression and Functionmentioning
confidence: 99%
“…Next-generation sequencing technology has greatly accelerated progress in functional genomics (Huang et al, 2010;Werner, 2010;Li et al, 2018), allowing quantitative trait locus (QTL) mapping and genome-wide association studies (GWASs) (Xiao et al, 2017) to become powerful tools for elucidating the genetic architecture of complex traits (Atwell et al, 2010;Huang et al, 2010;Tian et al, 2011;Wang et al, 2018a;Zhang et al, 2019a), and many genes governing important agronomic traits have been identified (Zuo and Li, 2014;Yao et al, 2018;Fernie and Yan, 2019;Shi et al, 2019). For example, before 2000, only approximately 130 genes had been cloned in rice.…”
Section: Introductionmentioning
confidence: 99%
“…Heading date regulation networks mainly involve vernalization, photoperiod, and hormones (such as gibberellin) [ 1 , 2 ]. There are three important regulatory genes in the vernalization pathway: Vernalization1 ( Vrn1-5 A , Vrn1-5B , Vrn1-5D ) [ 3 6 ], Vernalization2 ( Vrn2 ) [ 1 , 4 ], and Vernalization3 ( Vrn3 ) [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%